A política de defesa do Japão na primeira década do Século XXI - Watanabe, Paulo Daniel [UNESP] (2016)
The way Japan entered the international community after its defeat in World War II makes it a unique model in the international relations. After the end of the Japanese Empire, Japan has gone through many changes that impacted its foreign policy during the next 50 years. After restoring its sovereignty in 1952 and under a constitutional ban on any armed forces, Japan formulated its foreign and defense policy centered in the US, under a subordinated role, as a free rider. It was expected, however, that such condition would not last for a long time. It was expected that Japan would turn into a military power after being a economic power. At the end of the 20th century, Japan did not reach the role that was foreseen. Nevertheless, from 2001 on, Japan started a revisionist policy, which has changed concepts, theories and characteristics that described the Japanese foreign policy. Japan then decided to change its behavior in defense and it was welcomed by the US. This thesis analyses the defense policy of Japan and its main changes during the first decade of the 21st century.